The Interplay Between Absolute Language and Moral Reasoning on Endorsement of Moral Foundations - Blankenship, Kevin L.; Craig, Traci Y.; Machacek, Marielle G. (Frontiers in Psychology, 2021)
Morality – the subjective sense that humans discern between right and wrong – plays a ubiquitous role in everyday life. Deontological reasoning conceptualizes moral decision-making as rigid, such that many moral choices are forbidden or required. Not surprisingly, the language used in measures of deontological reasoning tends to be rigid, including phrases such as “always” and “never.” Two studies (N = 553) drawn from two different populations used commonly used measures of moral reasoning and measures of morality to examine the link between individual differences in deontological reasoning and language on the endorsement of moral foundations. Participants low on deontological reasoning generally showed less endorsement for moral principles when extreme language was used in the measures (relative to less extreme language).